Validity and Inter-rater Reliability of the Scoring Rubrics for the Science Teacher TPACK Test Instrument - Permana, Raden Ahmad Hadian Adhy; Widodo, Ari (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
This study examined the content validity of the scoring rubric instrument for measuring science teachers’ TPACK and the inter-rater reliability in using the instrument. This research was conducted as part of research and development which has been designed for the development of instruments for measuring teacher knowledge. The analysis carried out was a qualitative analysis based on triangulation of the three validators’ validation results and quantitative analysis for inter-rater reliability based on the Intraclass Correlation Coefficient (ICC) obtained for each question. The validation involved three science education experts from the university to assess the suitability of the scoring rubrics in the technological pedagogical content knowledge (TPACK) framework. Inter-rater reliability examining involved 100 participants who answered 15 questions on the instrument and three experienced raters to assess the participants' answers. The validation results showed that the instrument content was valid for measuring the knowledge tested and had very high inter-rater reliability coefficient for all items The validation results show that qualitatively the contents of the instrument are valid for measuring the knowledge being tested and had an average inter-rater reliability coefficient of 0.94 (very high).